The Legal Liability of Local Governments in Disputes Over Athlete Bonus Payments - Muhammad Bara’ Ramadhan M; Wahyu Prawesthi; Muhammad Yustino Aribawa; Dedi Wardana Nasoetion (UNIVERSITAS PAKUAN, 2026)
This study examines the legal liability of local governments for failing to fulfil promised bonus payments to athletes. This issue arises because, while bonuses are promised as recognition of athletes’ achievements, in practice, payments are often delayed or fail to materialise. The objective of this legal study is to describe and explain in detail and fundamentally that, based on the principle of legal certainty, the principles of good governance, and statutory provisions, local governments can be held legally liable for breach of contract or negligence in fulfilling promises to pay athlete bonuses. This study is a normative, descriptive-analytical research study, utilising secondary data through a literature review and qualitative data analysis. The results of the study indicate that athlete bonuses promised by local governments carry binding legal and administrative consequences once formalised in policies, decisions, or local budgets. Therefore, athletes, as aggrieved parties, are entitled to legal protection through administrative mechanisms or legal action in accordance with applicable laws and regulations. Keywords: Accountability, Government, Bonuses, Athletes, Disputes.